1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
IxI=0;
Если x = 0, то |0| = 0;
IxI=x
Любое значение x >= 0
IxI=-x
Любое значение x < 0
Ix^5I=-x^5
Любое значение x^5 < 0, значит x < 0
I-xI^4=x^4
Любое значение x >= 0
I-xI^7=x^7
Любое значение x >= 0